2008
DOI: 10.3382/ps.2007-00466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Housing System and Cold Stress on Heterophil-to-Lymphocyte Ratio, Fluctuating Asymmetry, and Tonic Immobility Duration of Chickens

Abstract: The purpose of this study was to analyze the effect of housing system and cold stress on the heterophil-to-lymphocyte ratio, the fluctuating asymmetry, and the tonic immobility duration of chickens. In experiment 1, hens (n=120; 36 wk old) from 5 Spanish breeds and a White Leghorn population, which had been housed in pens with or without access to an outdoor area from 20 wk of age, were used. The effect of housing system on heterophil-to-lymphocyte ratio varied from breed to breed, differences between housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 23 publications
3
39
0
2
Order By: Relevance
“…Some study showed that genotypes had considerable variations in terms of TI (Campo et al, 2000). In the present study TI of slow-growing broilers had excessively lower (ranged 57.70 to 93.77 s) with outdoor access than those (ranged 158 to 398 s) of Campo et al (2008), who tested six different Spanish breeds. Likewise, Prieto and Campo (2010) stated that TI found 99 s in White Leghorn reared with standard temperatures.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Some study showed that genotypes had considerable variations in terms of TI (Campo et al, 2000). In the present study TI of slow-growing broilers had excessively lower (ranged 57.70 to 93.77 s) with outdoor access than those (ranged 158 to 398 s) of Campo et al (2008), who tested six different Spanish breeds. Likewise, Prieto and Campo (2010) stated that TI found 99 s in White Leghorn reared with standard temperatures.…”
Section: Discussionmentioning
confidence: 45%
“…Besides, they are subjected to various factors as well as infectious and parasitic diseases, social interactions and unfavourable climatic conditions that may expand both stress and fear reactions and depress wellbeing. As criteria for measuring levels of stress, welfare and fear in chickens is predicted to duration of tonic immobility (TI) and fl uctuating asymmetry (FA) (Campo et al, 2008;Dávila et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a genetic component to heterophils and lymphocytes responses to stressors [59]. Bayyari et al [60] reported that lymphocyte numbers were lower in a line of turkeys selected for heavier BW than in a line selected for increased egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Fear is an adaptive response, but it can also be undesirable if it results in extreme distress or injury or if it is chronic (Jones, 1996). Several studies have been conducted to compare levels of fear in different housing systems as an indicator of hen welfare in those systems (Hansen et al, 1993;Colson et al, 2005;Campo et al, 2008;Graml et al, 2008). However, such studies are very difficult to interpret and extrapolate to commercial housing conditions.…”
Section: Welfare Concerns During Depopulation Of Specific Housing Sysmentioning
confidence: 95%